2010
DOI: 10.1163/18759866-07903003
|View full text |Cite
|
Sign up to set email alerts
|

The enigmatic Marmorkrebs (marbled crayfish) is the parthenogenetic form of Procambarus fallax (Hagen, 1870)

Abstract: A mysterious parthenogenetic cambarid crayfish (the Marmorkrebs) has been spreading across the globe for the past decade. We compare this crayfish directly to two other cambarids, Procambarus fallax and P. alleni, that have been suggested to be related or even identical to the Marmorkrebs. Using external morphology and sequences of two mitochondrial genes we show clear correspondences between Marmorkrebs and P. fallax, a species found natively throughout peninsular Florida, USA. Based on these congruent result… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
117
0
4

Year Published

2010
2010
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 138 publications
(124 citation statements)
references
References 63 publications
3
117
0
4
Order By: Relevance
“…2006/656/EC concerning health conditions and certification requirements for imports of ornamental fish only. Today, it is extremely easy to buy, via aquarium trade fairs and internet sales, NICS for ornamental use, as shown in the case of both the marbled crayfish (Nonnis Peay 2009), a North American species recently identified as a parthenogenetic form of Procambarus fallax (Martin et al 2010), and the Australian red-claw crayfish C. quadricarinatus in the UK (Peay 2009). At present, in some European countries sale of NICS is legal and an aquarium wholesaler can sell NICS to anyone in Sweden, Ireland or other countries where the species are banned.…”
Section: An Overviewmentioning
confidence: 99%
“…2006/656/EC concerning health conditions and certification requirements for imports of ornamental fish only. Today, it is extremely easy to buy, via aquarium trade fairs and internet sales, NICS for ornamental use, as shown in the case of both the marbled crayfish (Nonnis Peay 2009), a North American species recently identified as a parthenogenetic form of Procambarus fallax (Martin et al 2010), and the Australian red-claw crayfish C. quadricarinatus in the UK (Peay 2009). At present, in some European countries sale of NICS is legal and an aquarium wholesaler can sell NICS to anyone in Sweden, Ireland or other countries where the species are banned.…”
Section: An Overviewmentioning
confidence: 99%
“…Its basic biology is rather well investigated Seitz et al 2005;Alwes and Scholtz 2006;Rieger and Harzsch 2008;Vogt 2008b, c;Farca Luna et al 2009Kawai et al 2009). Just recently it has been shown that the marbled crayfish is a parthenogenetic form of the slough crayfish Procambarus fallax (Hagen 1870; Martin et al 2010). This cambarid species is native to Florida and south Georgia and occurs in wetland, stream, ditch and pond habitats (Dorn and Volin 2009).…”
Section: Biology Of the Marbled Crayfish And Peculiarities Qualifyingmentioning
confidence: 99%
“…The marbled crayfish belongs to the decapod crustaceans, which include the commercially valuable shrimps, lobsters, crayfish and crabs. It was discovered in the mid-1990s in the German aquarium trade (Scholtz et al 2003;) and has only recently been identified as the parthenogenetic form of the slough crayfish, Procambarus fallax (HAGEN, 1870), which is native to Georgia and Florida, USA (Martin et al 2010a). Its scientific name is therefore Procambarus fallax (HAGEN, 1870) f. virginalis (Martin et al 2010a).…”
Section: What Is the Marmorkrebs?mentioning
confidence: 99%
“…It was discovered in the mid-1990s in the German aquarium trade (Scholtz et al 2003;) and has only recently been identified as the parthenogenetic form of the slough crayfish, Procambarus fallax (HAGEN, 1870), which is native to Georgia and Florida, USA (Martin et al 2010a). Its scientific name is therefore Procambarus fallax (HAGEN, 1870) f. virginalis (Martin et al 2010a). The marbled crayfish is the only one of more than 10000 decapods that produces high amounts of genetically identical offspring by obligatory parthenogenesis (Martin et al 2007;Vogt et al 2008).…”
Section: What Is the Marmorkrebs?mentioning
confidence: 99%